2012
DOI: 10.1111/j.1469-8137.2012.04089.x
|View full text |Cite
|
Sign up to set email alerts
|

13C pulse‐labeling assessment of the community structure of active fungi in the rhizosphere of a genetically starch‐modified potato (Solanum tuberosum) cultivar and its parental isoline

Abstract: Summary The aim of this study was to gain understanding of the carbon flow from the roots of a genetically modified (GM) amylopectin‐accumulating potato (Solanum tuberosum) cultivar and its parental isoline to the soil fungal community using stable isotope probing (SIP). The microbes receiving 13C from the plant were assessed through RNA/phospholipid fatty acid analysis with stable isotope probing (PLFA‐SIP) at three time‐points (1, 5 and 12 d after the start of labeling). The communities of Ascomycota, Basid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
89
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 65 publications
4
89
0
Order By: Relevance
“…Therefore, microorganisms have been broadly used to determine the possible effects of genetically modified (GM) plants on the soil environment. Some authors have indeed reported modifications in the structure, composition, and abundance of particular (nontarget) microbial groups (6,7). However, these effects were, in general, quite transient (6,8,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, microorganisms have been broadly used to determine the possible effects of genetically modified (GM) plants on the soil environment. Some authors have indeed reported modifications in the structure, composition, and abundance of particular (nontarget) microbial groups (6,7). However, these effects were, in general, quite transient (6,8,9).…”
mentioning
confidence: 99%
“…These relationships are often specific, suggesting that changes in plant genotype can have an impact on the association of specific microbial groups with plants, thus altering the composition of the rhizosphere microbiome (2). Based on this premise, several authors have suggested that genetic modifications of plants may modulate rhizosphere biodiversity and possibly impact the functioning of the rhizosphere (4)(5)(6). Therefore, microorganisms have been broadly used to determine the possible effects of genetically modified (GM) plants on the soil environment.…”
mentioning
confidence: 99%
“…CO2 pulse-chase experiments are amongst the most widely applied, designed to deliver 13 C-labelled root exudate derived from newly formed 13 C-photosynthate to explore C allocation from plants to the below-ground biomass [Leake et al, 2006;Jin and Evans, 2010;Hogberg et al, 2010;Ladygina and Hedland, 2010;Hannula et al, 2012;Yao et al, 2012;Dirgo et al, 2013;Tavi et al, 2013;Bahn et al, 2013;Dias et al, 2013;Balasooriya et al, 2014;Malik et al, 2015]. In both categories 13 C-PLFAs are the most commonly investigated biomarkers with time-courses varying widely (days to years) to provide temporal and quantitative insights into the processing of 13 C-labelled substrates by the soil microbial community, often in response to changes in particular environmental variables e.g.…”
mentioning
confidence: 99%
“…In soil, the rhizosphere is a "hot-spot" of microbial activity, where approximately 20 to 40% of the phytosynthetic carbon fixed by a plant is released as root exudates (Jones et al 2009;Philippot et al 2013). For a long time, it has been assumed that the rhizosphere is mainly dominated by bacteria, however, recent studies revealed significant utilization of root exudates by saprotrophic fungi (Hannula et al 2012). Therefore, fungal-bacterial interactions as the one described in this study may take place in the rhizosphere and have an effect on the rhizosphere microbiome, which consequently, may play an important role for plant growth and health.…”
Section: Discussionmentioning
confidence: 99%
“…However, also saprotrophic (i.e. organotrophic) fungi abundant in the rhizosphere significantly contribute to the degradation of root-exudates (Treonis et al 2004;Denef et al 2007;Buée et al 2009;Hannula et al 2012). Hence, organotrophic bacteria and fungi must have developed adequate strategies to survive and thrive in the rhizosphere.…”
Section: The Rhizosphere -An Oasis For Microbial Life Belowgroundmentioning
confidence: 99%